Impact of New-Onset Persistent Left Bundle Branch Block on Reverse Cardiac Remodeling and Clinical Outcomes After Transcatheter Aortic Valve Replacement - Kim, Kyu; Ko, Young-Guk; Shim, Chi Young; Ryu, JiWung; Lee, Yong-Joon; Seo, Jiwon; Lee, Seung-Jun; Cho, Iksung; Hong, Sung-Jin; Ahn, Chul-Min; Kim, Jung-Sun; Kim, Byeong-Keuk; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The clinical implication of new-onset left bundle branch block (LBBB) after transcatheter aortic valve replacement (TAVR) remains controversial. We investigated the impact of new-onset persistent LBBB on reverse cardiac remodeling and clinical outcomes after TAVR. Methods: Among 478 patients who had undergone TAVR for symptomatic severe aortic stenosis from 2011 to 2021, we analyzed 364 patients after excluding patients with pre-existing intraventricular conduction disturbance or a pacing rhythm before or during the indexed hospitalization for TAVR. Echocardiographic variables of cardiac remodeling at baseline and 1 year after TAVR were comprehensively analyzed. The primary outcome was a composite of cardiovascular death and hospitalization for heart failure. Secondary outcomes were all-cause death and individual components of the primary outcome. Result: New-onset persistent LBBB occurred in 41 (11.3%) patients after TAVR. The no LBBB group showed a significant increase in the left ventricular (LV) ejection fraction and decreases in LV dimensions, the left atrial volume index, and LV mass index 1 year after TAVR (all p<0.001). However, the new LBBB group showed no significant changes in these parameters. During a median follow-up of 18.1 months, the new LBBB group experienced a higher incidence of primary outcomes (hazard ratio [HR]: 5.03; 95% confidence interval [CI]: 2.60-9.73; p < 0.001) and all-cause death (HR: 2.80; 95% CI: 1.38-5.69; p = 0.003). The data were similar after multivariable regression analysis. Conclusion: New-onset persistent LBBB after TAVR is associated with insufficient reverse cardiac remodeling and increased adverse clinical events.